Investigating the characteristics and needs of frequently admitting hospital patients: a cross-sectional study in the UK - John Chang; Anuj Sharma; Reem Kayyali; Gill Funnell; Bassel Odeh; Yannis Katsaros; Shereen Nabhani-Gebara; Barbara Pierscionek; Joshua Sterling Wells (BMJ Open)
Objectives This study forms the user requirements phase of the OPTIMAL project, which, through a predictive model and supportive intervention, aims to decrease early hospital readmissions. This phase aims to investigate the needs and characteristics of patients who had been admitted to hospital ≥2 times in the past 12 months.Setting This was a cross-sectional study involving patients from Croydon University Hospital (CUH), London, UK.Participants A total of 347 patients responded to a postal questionnaire, a response rate of 12.7%. To meet the inclusion criteria, participants needed to be aged ≥18 and have been admitted ≥2 times in the previous 12 months (August 2014–July 2015) to CUH.Primary and secondary outcomes To profile patients identified as frequent admitters to assess gaps in care at discharge or post-discharge. Additionally, to understand the patients’ experience of admission, discharge and post-discharge care.Results The range of admissions in the past 12 months was 2–30, with a mean of 2.8. At discharge 72.4% (n=231/347) were not given a contact for out-of-hours help. Regression analysis identified patient factors that were significantly associated with frequent admissions (>2 in 12 months), which included age (p=0.008), being in receipt of care (p=0.005) and admission due to a fall (p=0.01), but not receiving polypharmacy. Post-discharge, 41.8% (n=145/347) were concerned about being readmitted to the hospital. In the first 30 days after discharge, over half of patients (54.5% n=189/347) had no contact from a healthcare professional.Conclusion Considering that social care needs were more of a determinant of admission risk than medical needs, rectifying the lack of integration, communication and the under-utilisation of existing patient services could prevent avoidable problems during the transition of care and help decrease the likelihood of hospital readmission.